Model Regresi Linear Produksi Padi di Indonesia dengan Estimasi-M - Hasih Pratiwi; Yuliana Susanti; Monaluvy Septiningrum (Limits: Journal of Mathematics and Its Applications, 2007)
Policy of the price of main food is one of important instrument in creating resilience of national food. Remembering the importance of accomplishment e®ort of requirement of food, especially paddy, it is required an effort to predict production in future. There are some methods which are applicable to predict the production of paddy and to investigate the factors influencing it; one of them is regression analysis. An estimation method which is applicable to determine the regression model is M-estimation. This estimation is an extension of maximum likelihood method and robust estimation, where its estimation value is not influenced by small change in data. The purpose of this research is to determine the regression model to predict the production of paddy in Indonesia using estimation M. Based on the result of research we conclude that the prediction model for production of paddy in Indonesia with M-estimation is by = ¡92; 790 + 5; 02x1 + 6; 37x2: The increment of one hectare farm wide and one ton seed will increase production of paddy 5.03 tons and 6.23 tons respectively. The regression parameter signi¯cance test shows that the farm wide influences the production of paddy significantly.